2019
DOI: 10.1161/strokeaha.119.025033
|View full text |Cite
|
Sign up to set email alerts
|

S100B Serum Elevation Predicts In-Hospital Mortality After Brain Arteriovenous Malformation Rupture

Abstract: B rain arteriovenous malformation (BAVM) rupture is the leading cause of morbidity and mortality in this disease. Predicting outcome after BAVM rupture has mainly relied on demographic, clinical, and imaging markers. 1 S100B serum level elevation has been found to be associated with severity of neurological insult in neurocritically ill patients. 2 The present study aimed to determine whether elevation of S100B is associated with in-hospital mortality after BAVM rupture. Methods Data Availability Study data ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
(9 reference statements)
0
8
0
Order By: Relevance
“…Elevated S100B serum within 48 h following admission has been found to be an independent predictor of in-hospital mortality in ruptured BAVM, stronger than imaging markers [2]. The present study provides an extended S100B protein levels analysis with data obtained within the first month of admission.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Elevated S100B serum within 48 h following admission has been found to be an independent predictor of in-hospital mortality in ruptured BAVM, stronger than imaging markers [2]. The present study provides an extended S100B protein levels analysis with data obtained within the first month of admission.…”
Section: Discussionmentioning
confidence: 73%
“…Records of adult patients (age >15 years old) with BAVM ruptures, admitted to a tertiary care teaching center between 1 January 2003, and 1 February 2020, were retrospectively reviewed. One hundred and ninety-two ruptures included in this study were previously included in a report of early S100B protein levels after BAVM ruptures [2]. Demographic, clinical, biological, and imaging characteristics of patients were reviewed.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the classic Spetzler-Martin (SM) grading system [17], supplementary scale [18], and even with evolving fMRI-based HDVL grading scale combined with lesion-to eloquence distance (LED) are added [19], the evaluation becomes accurate but tedious at the same time. And there are some objectively advanced biomarkers, such as S100B, matrix metalloproteinase-9 (MMP-9), interleukin-1 beta (IL-1β), vascular endothelial growth factor (VEGF), and N6-methyladenosine methyltransferase 3 (METTL3) [12,[20][21][22], which were proposed to be the predictors for the in-hospital complications and neurological outcomes. However, these indicators were unable to directly provide guidance for clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, previous studies have focused on hemorrhagic stroke and unfavorable outcomes [5,6]. Moreover, some studies suggested that Hcy disorders and hemorrhagic bAVMs shared similar underlying mechanisms in terms of hemodynamics [7][8][9] and molecular abnormalities [10][11][12][13][14]. However, the above-mentioned studies were based on other hemorrhagic subtypes and animal experiments; the clinical significance of Hcy in patients with bAVM has not been discussed yet.…”
Section: Introductionmentioning
confidence: 99%